2007
DOI: 10.1159/000110741
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injuries in Children and Young Adults: A Birth Cohort Study from Northern Finland

Abstract: Aims: Incidence and mortality rates of traumatic brain injury (TBI) were investigated by using the Northern Finland Birth Cohort. This cohort provides a valuable source of data from the population born in 1966 (n = 12,058) in the 2 northernmost provinces of Finland. Methods: The cohort was followed for 34 years, and data were gathered from the Finnish Hospital Discharge Register and the Registry for Causes of Death by Statistics Finland. Results: The annual incidence of and mortality from TBI were 118 and 14/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 52 publications
1
19
1
Order By: Relevance
“…This is supported by previous reports [17,64] that the incidence of paediatric TBI in Iceland is similar to other western countries and by the present 7.6% prevalence of having been hospitalized with TBI, which is comparable to the 4-12% reported elsewhere [18,23,30]. The findings have important implications for injury prevention, healthcare planning, cognitive health concerns and compensation issues.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is supported by previous reports [17,64] that the incidence of paediatric TBI in Iceland is similar to other western countries and by the present 7.6% prevalence of having been hospitalized with TBI, which is comparable to the 4-12% reported elsewhere [18,23,30]. The findings have important implications for injury prevention, healthcare planning, cognitive health concerns and compensation issues.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of reported TBI-related long-term disability is also distinctly higher than previously suggested [10,14,23,[30][31][32].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The mean incidence rate of hospitalized and fatal TBI and the average mortality rate have been reported as 235 per 100,000 and about 15 per 100,000, respectively, in Europe [1]. Winqvist et al reported that by the age of 35, 3.8% of the subjects in their northern Finland birth cohort study had experienced at least one hospitalization for TBI [2]. A huge number of people are seen in emergency departments; the great majority of them, about 235,000 each year, are hospitalized because of non-fatal TBI, and approximately 50,000 die according to reports from the United States [3].…”
Section: Introductionmentioning
confidence: 99%